Blockchain-Based Traceability Systems for Arabica Coffee Supply Chains: Economic Impact Analysis in Gayo Highland Farmers, Aceh Province - Purnama Sari, Anisa (Politeknik Siber Cerdika Internasional, 2025)
This study investigates blockchain-based traceability implementation among smallholder Arabica coffee farmers in Gayo Highlands, Aceh Province, Indonesia. Using mixed-methods quasi-experimental design, 150 treatment farmers adopting blockchain technology and 150 control farmers with traditional practices were tracked over 18 months (January 2024–June 2025). Data encompassed structured surveys (three time points), blockchain transaction records (2,847 coffee lots), semi-structured interviews (60 stakeholders), and focus groups (52 participants). Difference-in-differences regression revealed statistically significant price premiums of USD 0.35/kg attributable to blockchain (p < 0.001), yielding USD 356 average annual household income increases (13.0% gain). Enhanced market access emerged with 41% of treatment farmers establishing new buyer relationships versus 12% control farmers (χ² = 28.4, p < 0.001), and supply chain disintermediation reduced intermediary stages from 4.3 to 3.1. Implementation challenges included infrastructure constraints (62% connectivity issues), digital literacy gaps (41% requiring assistance), and heterogeneous impacts favoring larger farms and higher-quality producers. Findings demonstrate that appropriately designed blockchain systems generate measurable economic benefits for smallholder producers while requiring sustained capacity building, complementary infrastructure investments, and equitable governance frameworks for successful technology adoption in developing agricultural contexts.